Covalent organic framework-cadmium sulfide hybrid as a prototype photocatalyst for visible-light-driven hydrogen production - Thote, Jayshri; Aiyappa, Harshitha Barike; Deshpande, Aparna; Diaz, David Diaz; Kurungot, Sreekumar; Banerjee, Rahul (Chemistry A-European Journal, 2014)
CdS nanoparticles were deposited on a highly stable, two-dimensional (2D) covalent organic framework (COF) matrix and the hybrid was tested for photocatalytic hydrogen production. The efficiency of CdS-COF hybrid was investigated by varying the COF content. On the introduction of just 1 wt% of COF, a dramatic tenfold increase in the overall photocatalytic activity of the hybrid was observed. Among the various hybrids synthesized, that with 10 wt% COF, named CdS-COF (90: 10), was found to exhibit a steep H2 production amounting to 3678 mmolh(-1) g(-1), which is significantly higher than that of bulk CdS particles (124 mmolh(-1)g(-1)). The presence of a p-conjugated backbone, high surface area, and occurrence of abundant 2D hetero-interface highlight the usage of COF as an effective support for stabilizing the generated photoelectrons, thereby resulting in an efficient and high photocatalytic activity.
Keywords: charge transfer; covalent organic frameworks; hybrid materials; hydrogen production; Photocatalysis

Cobalt-modified covalent organic framework as a robust wateroxidation electrocatalyst - Aiyappa, Harshitha Barike; Thote, Jayshri; Shinde, Digambar Balaji; Banerjee, Rahul; Kurungot, Sreekumar (Chemistry of Materials, 2016)
The development of stable, efficient oxygen evolution reaction (OER) catalyst capable of oxidizing water is one of the premier challenges in the conversion of solar energy to electrical energy, because of its poor kinetics. Herein, a bipyridine-containing covalent organic framework (TpBpy) is utilized as an OER catalyst by way of engineering active Co(II) ions into its porous framework. The as-obtained Co-TpBpy retains a highly accessible surface area (450 m(2)/g) with exceptional stability, even after 1000 cycles and 24 h of OER activity in phosphate buffer under neutral pH conditions with an overpotential of 400 mV at a current density of 1 mA/cm(2). The unusual catalytic stability of Co-TpBpy arises from the synergetic effect of the inherent porosity and presence of coordinating units in the COF skeleton.

Constructing covalent organic frameworks in water via dynamic covalent bonding - Thote, Jayshri; Aiyappa, Harshitha Barike; Kumar, Raya Rahul; Kandambeth, Sharath; Biswal, Bishnu P.; Shinde, Digambar Balaji; Roy, Neha Chaki; Banerjee, Rahul (Iucrj, 2016)
The formation of keto-enamine based crystalline, porous polymers in water is investigated for the first time. Facile access to the Schiff base reaction in water has been exploited to synthesize stable porous structures using the principles of Dynamic Covalent Chemistry (DCC). Most credibly, the water-based Covalent Organic Frameworks (COFs) possess chemical as well as physical properties such as crystallinity, surface area and porosity, which is comparable to their solvothermal counterparts. The formation of COFs in water is further investigated by understanding the nature of the monomers formed using hydroxy and non-hydroxy analogues of the aldehyde. This synthetic route paves a new way to synthesize COFs using a viable, greener route by utilization of the DCC principles in conjunction with the keto-enol tautomerism to synthesize useful, stable and porous COFs in water.